Addiction and the itch‐scratch cycle. What do they have in common?. Issue 12 (30th September 2019) - Ishiuji, Yozo
Abstract: Itch is a multidimensional experience involving various brain regions associated with sensory perception and emotion, as well as an urge to scratch employing the motor system. Scratch temporarily relieves itch sensation in healthy subjects. However, in patients with chronic itch, rather than inhibit, scratch may aggravate itch. Patients with chronic itch, such as those with atopic dermatitis, experience severe itch and a strong desire to scratch. This urge to scratch is the driving force underlying the formation of the itch‐scratch‐cycle, an addictive and vicious cycle in chronic itch patients. This vicious itch‐scratch behaviour and various types of addiction (henceforth, including recreational drug use) were shown to share common sensory mechanisms. Abnormalities have been observed in central neural circuits, including the reward, motivation/drive, control and learning/memory circuits, as well as other brain systems. Reward systems, including the ventral tegmental area (VTA), nucleus accumbens (NAc) and striatum, are important for brain processing of both addiction and itch. In addition to reward, addicted individuals can experience severe disruptions in motor control, cognitive awareness, executive function, learning/memory and even emotional functions. Findings showing that addiction and itch share a common neurobiological foundation could have important mechanistic and therapeutic implications. Here we propose that similar neuroadaptations exist in addiction and chronic itch patients.